Environmental Sanitation Challenges and Opportunities in Indonesia Coastal Regions: A Review - Abdul Rahman; Andi Isnaeni (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Coastal areas present distinct challenges and characteristics that differentiate them from inland regions. These include issues related to substandard housing, limited access to healthcare services, and environmental factors that contribute to both economic and public health problems. Environmental sanitation is a critical component, as poor sanitation in coastal communities often leads to increased vulnerability to disease and reduced quality of life. Monitoring environmental factors that influence human health is essential in these regions, where infrastructure and services are frequently inadequate. Objective: This study aims to provide a comprehensive overview of environmental sanitation conditions in coastal areas of Indonesia. Methods: A Systematic Literature Review (SLR) approach was employed to collect and analyze relevant scholarly articles from online databases, particularly Google Scholar and ResearchGate. The selection process followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Articles published between 2020 and 2024 were included, using keywords such as